ANALISIS PERFORMA KENDARAAN UTAMA PKP-PK FT 11 DALAM MENUNJANG KESELAMATAN PENERBANGAN DI BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA - Riza Nuril Amri; Imam Sonhaji; Rahmawati Sukra (LPPM Politeknik Pratama, 2025)
This research analyzes the performance of the main Aircraft Rescue and Fire Fighting (ARFF) vehicle, Foam Tender (FT) 11 Oshkosh Striker 3000 from 2013, at Soekarno-Hatta International Airport. The role of ARFF is crucial in ensuring aviation safety, especially in handling aircraft accident and fire incidents. FT 11 is vital for minimizing impact and saving lives; periodic performance analysis is therefore essential for operational readiness according to strict international standards.The objective of this study is to evaluate the conformity of FT 11's performance with the Regulation of the Director General of Air Transportation Number KP 547 Year 2015 concerning Technical Operational Guidelines for Civil Aviation Safety Regulations, and to identify the impact of performance degradation on the overall operations of the ARFF unit at the airport. A qualitative research method was applied, with data collection through direct observation, in-depth interviews, and comprehensive documentation studies. This approach was chosen for its ability to understand factors influencing vehicle maintenance effectiveness, including technical skills, environmental factors, and policies, as well as to capture the perceptions and experiences of personnel in the field.The research findings are expected to present key findings related to the actual performance conditions of FT 11 based on applicable standard parameters, and to provide a comprehensive analysis of the implications of this performance on the readiness and responsiveness of the ARFF unit in emergency situations. The discussion will include an evaluation of the physical and functional condition of the vehicle, an analysis of the impact of performance degradation on operational efficiency, and an identification of gaps between actual conditions and established standards. Based on these findings, the research will formulate concrete recommendations for improving vehicle maintenance systems and enhancing personnel training programs to increase emergency preparedness and response effectiveness, which will ultimately support the improvement of aviation safety at Soekarno-Hatta International Airport..